Understanding Through the Click: How Social Media Guides or Misleads the Issue of Halal Products - Widyoretno Adiani (RSF Press, 2024)
The awareness and understanding of Halal issues have significantly increased in recent times due to the prevalent use of social media. Nevertheless, the abundance of information often leads to the guidance of understanding, yet its credibility occasionally remains in doubt. Based on this condition, this study explores the role of social media as a catalyst for driving understanding of Halal issues, alongside its role in spreading misled information and investigating the responses of Muslim individuals to this dynamic. Using a systematic literature review (SLR), this study encompassed an analysis of 20 recent research articles published between 2016 and 2023 that fulfilled the inclusion and exclusion criteria and quality assessment, focusing on the discussion of Halal issues across various social media platforms. The findings reveal multiple insights, notably emphasizing that social media serves as a mediator between religion, the market, and consumption in significant ways, particularly in fostering awareness of Halal products and issues. Moreover, the study sheds light on the sensitivity of Halal issues, which are deeply intertwined with individuals’ beliefs and religiosity, thereby eliciting strong reactions and prompting community resistance even in the absence of confirmed information. In addition to presenting insights, this study identified potential issues that warrant further investigation in future studies. These endeavors are intended to enhance understanding within the field of Halal Studies and provide practical insights for the Halal industry to better understand the needs and perspectives of the Muslim population in the digital age.